Sedimentary characteristics of hyperpycnites in a shallow lacustrine environment: A case study from the Lower Cretaceous Xiguayuan Formation, Luanping Basin, Northeast China. (24th July 2019) - Dou, Luxing; Hou, Jiagen; Song, Suihong; Zhang, Li; Liu, Yuming; Sun, Shuang; Li, Yongqiang; Wang, Xixin; Ren, Xiaoxu; Tang, Ying; Tian, Heng; Yang, Yuhua
Abstract : Hyperpycnites are extrabasinal turbidites related to hyperpycnal flows which form during river floods. Compared to intrabasinal turbidite systems in deep marine or lacustrine settings, hyperpycnites in shallow lakes settings are not understood. In this work, we studied the typical sedimentary characteristics of shallow lacustrine hyperpycnal flow deposits in outcrops of the Luanping Basin, Northeast China. Based on the sedimentary architecture and analysis of the facies associations in these outcrops, the hyperpycnites can be classified into the following three types: (a) bedload‐dominated erosional channel deposits, (b) bedload‐ and suspended‐load‐dominated channel‐to‐lobe transitional deposits, and (c) suspended‐load‐dominated lobe deposits. The erosional channels in proximal locations are filled by mud clasts, parallel‐laminated sandstones, massive sandstones, cross‐bedded sandstones, massive siltstones, and mudstones. The channel‐to‐lobe transitional deposits in a middle location are composed of parallel‐laminated sandstones, cross‐bedded sandstones, mud clasts near internal erosional surfaces, ripple cross‐bedded sandstones, massive siltstones, and mudstones. The lobe deposits in distal locations are composed of ripple cross‐bedded sandstones, massive siltstones, and mudstones. The sedimentary process of the shallow lacustrine hyperpycnal flows shows obvious response to periodic flood energy fluctuations. Gentle slope, small capacity of flood discharges and semiarid paleoclimate may be the possible reason for the observed sedimentary architecture of the shallow lacustrine hyperpycnal flow deposits. Therefore, this study offers new insights into the sedimentology of shallow lacustrine deposits in rift basins.